The interaction between learning and caring - the patient's narrative as a foundation for lifeworld-led reflection in learning and caring. Issue 4 (3rd July 2020) - Ekebergh, Margaretha; Lindberg, Elisabeth
ABSTRACT: In this article, we present a knowledge approach to the interaction between learning and caring, which should play a significant role in the challenge of promoting sustainable healthcare. This knowledge approach requires awareness of the interactions between learning and caring in caring contexts. The intention is to present an exploration of knowledge and theory development based on research with a lifeworld perspective within caring science didactics. We are illuminating issues concerning reflection and learning encounters in a caring context, which include key concepts such as the patient's narrative. A strategy for reflective learning and caring based on the lifeworld concept is presented. This strategy includes four main components: the encounter between general knowledge and the patient's lived world, the patient's narrative, caring relationship creation through interaction with the patient and reflection through supervision. All of these components are permeated by a reflective approach. We are also clarifying what it means to intertwine learning and caring in addition to how this process can be strengthened in caring practices to optimise patient care. Three components are particularly important in facilitating the intertwining of learning and caring in clinical practice, namely genuine meetings, sensitivity towards the patient's narrative and reflection during interactions.